Floral therapy: Floral essences kinde-Perú - Acosta M., Emma M. (2008)
The work is a style of research: "Research in Action," which is the small-scale intervention in the functioning of the real world and a clase examination of the effects of such intervention, the ultimate goal being to improve practice. How to improve the practice af floral therapy in our country? Have the input for the preparation of flower remedies and therefore at this stage I had to get 21 flower essences Peruvian natural resources, in order to access and availability of floral therapy. When we talk about therapy floral we are referring to the use of flower essences in the context of an overall program of health improvement, whether in professional practice in home care. Although the word " therapy" is used generally to mean the treatment and cure of diseases, the Greek root therapies had a broader meaning and spiritual service, " therapeutic related to the word, mea ning" care". lt ís in this sense oí service and care we' re ta lking abaut Aower therapy, is a way to nourish and sustain the health charities forces of nature, in the context of a full human attention and love of wisdom.